Student readiness in learning Arabic language based on blended learning - Norasyikin, Osman; Mohd Isa, Hamzah (2017)
Learning with technology or e-learning has been taking place in all areas of education including in learning and teaching of Arabic language. Despite the widespread use of e-learning for Arabic language, in line with the current technological advancements, the role of face-to-face classroom interactions must not be neglected. Face-to-face learning and e-learning have their own strengths. Hence, a combination of both elements in teaching and learning as afforded by blended learning may be an excellent choice. This study seeks to identify student readiness in learning Arabic language based on blended learning approach among students at university level. The research took place at University Sultan Zainal Abidin (UniSZA), Malaysia involving 248 students. The students were asked to answer the distributed questionnaires. The questionnaires used 1-5 points Likert scale which are strongly not agree, not agree, not sure, agree and strongly agree. The need analysis encompassed the presence of facilities supporting blended learning, the internet and e-learning literacy among students and their readiness to adopt blended learning. The findings highlight the important roles played by both the students and the institution in providing facilities needed to support blended learning. The findings also reported that the existing facilities are in a state of readiness for the implementation of blended learning. The institution provides wireless connection throughout the campus while 96% of the students own a laptop. In addition, students are also discovered to be internet-savvy besides displaying readiness to adopt blended learning. Further studies are recommended in exploring how to design and develop successful blended learning in teaching and learning Arabic language.